Numerical Modeling of Elastic Wave Propagation in a Fluid-Filled Borehole (Communications in Computational Physics, 2008)
We review the methods of simulating elastic wave propagation in a borehole. We considered two different approaches: a quasi-analytic approach using the Discrete Wavenumber Summation Method, and the purely numerical Finite Difference Method. We consider the special geometry of the borehole and discuss the problem in cylindrical coordinates. We point out some numerical difficulties that are particularly unique to this problem in cylindrical coordinates.